Clinical adoption of robotics in endoscopy: Challenges and solutions. Issue 5 (9th September 2020) - Kaan, Hung Leng; Ho, Khek Yu
Abstract: The endoscope was traditionally used as a diagnostic instrument. In past decades, it has increasingly been adapted for therapeutic intents. Subsequently, the master–slave robotic concept was introduced into the field of endoscopy to potentially reduce the difficulty and complication rates of endoscopic therapeutic procedures. As interest in robotic endoscopy intensified, progressively more robotic endoscopic platforms were developed, tested, and introduced. Nevertheless, the future of robotic endoscopy hinges on the ability to meet specific clinical needs of procedurists. Three aspects are vital in ensuring continued success and clinical adoption of the robotic endoscope—demonstration of clinical safety and cost‐efficacy of the device, widespread availability of directed training opportunities to enhance technical skills and clinical decision‐making capabilities of the procedurist, and continued identification of new clinical applications beyond the current uses of the device. This review provides a brief discussion of the historical development of robotic endoscopy, current robotic endoscopic platforms, use of robotic endoscopy in conventional therapeutic endoscopic procedures, and the future of robotic endoscopy. Abstract : A successful robotic endoscope must provide beyond the basic requirement of a high functioning endoscopic resection tool. It must be demonstrated to be safe, and cost‐effective for its intended clinical application. Training can be best achieved through the synergy of artificial‐intelligence‐guided deep learning systems and virtual reality. Natural Orifice Transluminal Endoscopic Surgery (NOTES) is an ideal choice for the application of the robotic endoscope as the triangulation afforded by the device effectively solves the challenges faced when performing NOTES using existing endoscopic equipment.